2021
DOI: 10.47489/pszmc-806-35-3-37-43
|View full text |Cite
|
Sign up to set email alerts
|

Tamarix dioica (Ghaz) Protective Potential in the Carbon Tetrachloride-Induced Hepatotoxicity Animal Model

Abstract: Introduction: Hepatic diseases remain the leading cause of death worldwide. Despite overall advancements in health care, mortality due to hepatic diseases is constantly growing. More than 2 million people globally are estimated to die each year from liver diseases, and current treatment offers little for its management. Thus, it is essential to find more effective and less toxic pharmaceutical alternatives for the treatment of liver diseases. Aims & Objectives: Tamarix dioica, a shrub broadly used in herba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…It can be applied topically to treat skin conditions like eczema and anal fissure [13]. Biological studies have demonstrated that some Tamarix species can be used as anti-Alzheimer [15], anti-diabetic [16], anti-hyperlipidemic [17], anti-inflammatory [18,19], antimicrobial [20,21], antinociceptive [22], antioxidant [23], anti-coagulation [24], anti-rheumatoid [25], cytotoxicity [26], hepatoprotective [27] and wound healing [28] activities. Tamarix is represented in Egypt with two indigenous species which are T. aphylla (L.) H. Karst and T. nilotica (Ehrenb.)…”
Section: Introductionmentioning
confidence: 99%
“…It can be applied topically to treat skin conditions like eczema and anal fissure [13]. Biological studies have demonstrated that some Tamarix species can be used as anti-Alzheimer [15], anti-diabetic [16], anti-hyperlipidemic [17], anti-inflammatory [18,19], antimicrobial [20,21], antinociceptive [22], antioxidant [23], anti-coagulation [24], anti-rheumatoid [25], cytotoxicity [26], hepatoprotective [27] and wound healing [28] activities. Tamarix is represented in Egypt with two indigenous species which are T. aphylla (L.) H. Karst and T. nilotica (Ehrenb.)…”
Section: Introductionmentioning
confidence: 99%